MAKSIMALISASI POTENSI PENINGKATAN PENDAPATAN RUMAHTANGGA MELALUI PENGENALAN HOME INDUSTRI PADA KAUM PEREMPUAN DI DESA - Sumedi P Nugraha (UII, 2013)
The poverty rate that has not shown a significantdecline in Indonesia requires areorientation of approach associated method more comprehensive poverty reductionwith regard to the potential of a number of women in the population.Based onwriter’sobservations in the hamlet Cangkol Duwur, Lencoh village found that the averagewoman only worked there as an ordinary housewife, some have a farm to help herhusband. The low level of education makes them less able to compete if they want towork on important sectors in rural and urban areas. Seeing this, theauthors decided toperform a service in an effort to boost the economy with practical ways based ondomestic industry. This writer did considering this approach is an effective strategybecause it can encourage and stimulate mothers to generate more revenue with thecapital that is not too heavy and also access to a flexible work because it worked attheirown home.Besides the added value of their training and the introduction of homeindustry is because these activities do not require high levels of education because theseactivities are focused on the practical skills that are easily learned and applied ineveryday life.